Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
x = 0 , -2 , 1 +i√3 ; 1 - i√3
Step-by-step explanation:
2x⁴ + 16x = 0
2x(x³ + 8) = 0
2x(x³ + 2³) = 0
2x (x + 2)(x² -2x + 2²) = 0 {a³ + b³ = (a + b)*(a² -ab +b²}
2x = 0
x = 0
x + 2 = 0
x = -2
x² - 2x + 4 = 0
a = 1 ; b = -2 and c = 4
D = b² - 4ac = (-2)² - 4*1*4= 4 - 16 = -12
[tex]\sqrt{D} = \sqrt{-12}=\sqrt{2*2*3i^{2}}=2i\sqrt{3}[/tex]
root = (-b ± √D)/2a
= (-(-2) ± 2i√3)/2*1
= (2 ± 2i√2)/2
[tex]= \dfrac{2(1 + i\sqrt{3})}{2} \ ; \dfrac{2(1+i\sqrt{3})}{2}\\\\\\= 1 + i\sqrt{3} \ ; \ 1 - i\sqrt{3}[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.